2017
DOI: 10.1002/oby.21947
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response Comparison Between Parametric Human Models and Postmortem Human Subjects with a Wide Range of Obesity Levels

Abstract: The parametric human models have the capability to account for the obesity effects on the occupant impact responses and injury risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…It is recommended to use a modern seat belt system with shoulder and waist restraint that can effectively reduce body rotation. 55 Overall BMI and obesity were reported separately, that was the main limitation of the present study. The next constraint was to consider mortality in general and not to separate pre-hospital from the hospital deaths.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is recommended to use a modern seat belt system with shoulder and waist restraint that can effectively reduce body rotation. 55 Overall BMI and obesity were reported separately, that was the main limitation of the present study. The next constraint was to consider mortality in general and not to separate pre-hospital from the hospital deaths.…”
Section: Discussionmentioning
confidence: 82%
“…The presence of adipose tissue in the abdomen of the obese persons displaces seat belt from its normal position and increases the severity of the injury. 55 A study with consistent results showed that the compound fractures of the radius bone were higher with any increase in BMI. In spite of this fact, these individuals experienced less inability than normal weight persons.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, the parametric human modeling results show that body mass scaling does not appropriately account for variations in response due to body shape. To replace these outdated methods, we have presented preliminary results of subject-specific model validation, in which the human model was morphed into the geometry of specific cadavers Zhang, Cao, Wang, et al 2017). The morphed human models generally produce results with accuracy similar to that of the baseline model, but the biofidelity of the morphed human models certainly requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been applied to morph the THUMS v4 midsize male model into occupants with a wide range of stature and BMI (Hwang, Hallman, et al 2016;Shi et al 2015). The impact responses of those models were compared to cadaver tests through subject-specific validations Zhang, Cao, Wang, et al 2017). The same approach has also been applied to morph the GHBMC midsize male model into 100 human models with a wide range of age, stature, and BMI for both men and women (Zhang, Ca, Fanta, et al 2017).…”
Section: Introductionmentioning
confidence: 99%